Until debt do us part : subnational debt, insolvency, and markets - Canuto, Otaviano (World Bank Washington, D.C.US, 2013)
Surveys the reform experience of selected countries in strengthening subnational fiscal discipline and developing a framework for the resolution of subnational debt stress.Focusses on two types of debt restructuring, viz. national-government-led restructuring and the other central-government-led restructuring. Discusses the experiences of Cina, the Phillipines, Russia and South Africa in developing their subnational credit markets.